Peran Guru PPKN Dalam Pembentukan Sikap Nasionalisme Pada Siswa Kelas X IPS 1 di SMA Negeri 1 Roledelu - Yohanis Li; Abdullah Muis Kasim; Gisela Nuwa (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2024)
This study aims to determine the role of Civics Teachers in the Formation of Students’ Nationalism Attitudes at SMA Negeri 1 Roledelu in class X IPS 1This research was conducted at SMA Negeri 1 Roledelu in class X Social Studies Department in the second semester of the 2021/2022 academic year.The method used is a research method with a descritive quantitative approach.The results obtained indicate that the role of PPKn teachers is very important in increasing the nationalism attitudes of students at SMA Negeri 1 Roledelu, namely civics Teachers as mentors, Civics Teachers as bridges between generations, Civics Education teachers as a stimulus for creativity, and Civics Education teachers as authorities.